2021 IEEE/AIAA 40th Digital Avionics Systems Conference (DASC) 2021
DOI: 10.1109/dasc52595.2021.9594321
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Security of Unmanned Aerial Systems using Digital-Twin Technology and Intrusion Detection

Abstract: In this paper the general susceptibilities of Unmanned Aerial Vehicles (UAVs) against modern-cyber threats are explored and potential solutions proposed. This is achieved by applying digital-twin architectures and datadriven methods to UAVs to facilitate identification of real-time intrusions and anomalies. These concepts are validated by performing novelty detection on open access UAV flight data with GPS spoofing attacks, which represents a typical system use-case. Multiple machine learning models are traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Major companies like Airbus and Boeing are advancing digital twin technology [35]. However, research on integrating detection and avoidance systems within digital twin frameworks for UAM, particularly those involving LiDAR and UAV communication security, remains limited and presents an area ripe for exploration [36][37][38][39][40].…”
Section: Related Workmentioning
confidence: 99%
“…Major companies like Airbus and Boeing are advancing digital twin technology [35]. However, research on integrating detection and avoidance systems within digital twin frameworks for UAM, particularly those involving LiDAR and UAV communication security, remains limited and presents an area ripe for exploration [36][37][38][39][40].…”
Section: Related Workmentioning
confidence: 99%
“…Lv et al [82] developed a UAV DT to provide medical resources quickly and accurately to analyze the feasibility of UAV DTs during COVID-19 prevention and used DL algorithms to construct a UAV DT information forecasting model. Fraser et al [83] used DT and data-driven approaches to investigate the general susceptibilities of UAVs against contemporary cyber threats. Kapteyn et al [84] suggested a probabilistic graphical model representing the DT and its physical asset for a UAV using experimental data to calibrate the DT.…”
Section: Research Question Answersmentioning
confidence: 99%
“…It allows for monitoring and analysis at different levels, enabling engineers to assess the performance and health of specific components as well as understand the overall behavior and interactions within the system. Various research efforts have been conducted to use DT in UASs [3,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], addressing challenges and opportunities of UASs within this dynamic and evolving field. However, despite the significant discussion of DTs in the general aviation literature, especially in relation to manufacturing and maintenance, more effort and attention need to be devoted to the application of DTs in UASs [71].…”
Section: Introductionmentioning
confidence: 99%
“…Available studies have explored this technology for industrial applications using data analytics and ML technologies, such as the one-class support vector machine, local outlier factor, and deep unsupervised learning. For example, in [83], Fraser et al proposed DT architectural enhancements to improve the security of unmanned aerial systems. Gao et al [84] introduced an anomaly detection system to monitor abnormal behaviors in DT-based cyber-physical systems.…”
Section: Intrusion Detection Systems For Ev and Avmentioning
confidence: 99%